Scapholunate advanced collapse: a pictorial review - Tischler, Brian T.; Diaz, Luis E.; Murakami, Akira M.; Roemer, Frank; Goud, Ajay R.; Arndt, William F.; Guermazi, Ali (Insights into Imaging, 2014)
Scapholunate advanced collapse (SLAC) is the most common cause of osteoarthritis involving the wrist. Along with clinical investigation, radiological studies play a vital role in the diagnosis of SLAC wrist. Given that the osteoarthritic changes that are seen with SLAC occur in a predictable progressive pattern, it is important to understand the pathological evolution of SLAC to be able to recognise the associated progressive imaging findings seen with this disease process. Focusing on radiological findings, this article provides a pictorial review of the anatomy of the scapholunate interosseous ligament as well as the common terminology and biomechanical alterations seen in the pathway leading to the development of SLAC arthropathy. We will then discuss two additional common causes of SLAC wrist and their imaging findings, namely scaphoid non-union advanced collapse and calcium pyrophosphate dehydrate disease. In addition, we will provide a brief overview of the current treatment options of these pathological entities.o SLAC is the most common cause of osteoarthritis involving the wrist. o Arthritic changes of SLAC occur in a predictable progressive pathological and radiographic pattern. o Imaging is key for diagnosing, monitoring progression and assessing post-treatment changes of SLAC.
EVALuna2:14576